Photographic albums: self-representation and memory storage praxis in society - Hermanovska, Stella (IJRDO- Journal of Educational Research, 2017)
Albums are one of the most common types of memory storage. The objective of the abstract was to explore album phenomenon that has left an impression on society. The albums affected performed rituals in society, ranging from going to studio or taking photographs, album purchase and photography collecting and showing album to others. The album’s popularity is due to the availability of photography and its high distribution, as well as to scientific development, lifestyle and values. The album passed science achievement results: photography invention, the process development, the industrial revolution, which opened the way for the mass production goods move to market. The album was convenient and a visually aesthetic solution that buyers willingly bought and manufacturers, offered in the growing diversity of design, since nineteenth-century albums became a mass product. The content and typology of albums changed: at the beginning, society’s purpose was self-representation, but later, storytelling